Analisis Finansial Efiseinsi Manajemen Pembibitan Domba Garut (Ovis ares) - Agi Dahtiar; Nataliningsih Nataliningsih; Rian Susila (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
This research was conducted to (1) determine the performance of garut sheep farming. (2) Knowing the level of efficiency of Garut Sheep breeding farming in the Cibungur area. The research method used is a descriptive method with a qualitative and quantitative approach. The data collection technique used in this research is purposive sampling technique. The analysis technique used is descriptive analysis with a qualitative and quantitative approach. The results of the research show that Mr. Mamat, one of the activists in Garut sheep cultivation, keeps 15 sheep with 5 males and 10 females. In the sheep breeding business, the initial capital spent on 5 seeds and 1 male as well as medicines and then pens is IDR 57,869,528. The total revenue received from the sale of sheep potatoes was IDR. 47,500,000. The loss obtained by Mr. Mamat was Rp. -10,369,528. - The R/C Ratio result obtained was 0.82, with this value meaning that the Garut sheep breeding business carried out by Mr. Mamat was not suitable as a basic income, because from each one rupiah spent will result in a loss of 0.18 Rupiah.